UV Spectrophotometric Determination of Etoricoxib and Ezetimibe - Gowri Sankar, D.; Kumar, D.V.S.P.; Krishna, M.Vamsi; Latha, P.V.M. (Asian Journal of Chemistry, 2016)
Simple and sensitive UV spectrophotometric methods for the determination of Etoricoxib and Ezetimibe were having absorption maximum at 235 and 230 nm, respectively and these methods are extended to pharmaceutical preparations. There is no interference from any common pharmaceutical additives and diluents. The methods have been statistically evaluated and are found to be precise and accurate.